Cultural distance in international ventures : exploring perceptions of European and Chinese managers - Vaccarini, Katiuscia; Spigarelli, Francesca; Tavoletti, Ernesto; Lattemann, Christoph, 1970- (Palgrave Macmillan, 2017)
'This original book addresses the important issue of cultural distance and provides insights for the sustainable development of both the green technology industry and international collaboration. It does so with a multidisciplinary perspective and uses the cases of two highly relevant regions. It is a must-read for scholars and practitioners interested in the role of culture in Sino-European relations and green technology.' --Vasyl Taras, Associate Professor, University of North Carolina at Greensboro, USA This book uses the concepts of both cultural and psychic distance to analyse managers' perceptions in international business settings, with a specific focus on European and Chinese ventures in the green technology industry. The key concept of 'distance' refers to the variations of cultures, languages, business practices, policies and regulations that distinguish different countries. Offering empirical case studies and theoretical refinements on how scholars can conceptualise and operationalise the psychic distance construct, the authors provide a comprehensive examination of European foreign direct investment (FDI) to China and Chinese FDI to Europe. Contributing to the Marie Curie scheme, Partnering Opportunities between Europe and China in the Renewable Energy and Environmental iNdustries (POREEN), this book is an invaluable read for managers and practitioners.
Keywords: Investments, Foreign.; International business enterprises.; Cultural awareness.; Social psychology.; elektronické knihy; electronic books